Apply liberally: Towards a model of liberal management education - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2020)
Howard Thomas argues the case for integrating the liberal arts into management education so that the existing curricula emphasis on technological and analytical acumen is balanced with skills of critical thinking and ethical intelligence necessary for managerial judgment.